The Effect of Learning Quiz Team Strategy on the Reasoning Ability and Mathematical Learning Outcomes of Student in the Pandemic Era - Muhammad Rofik Siregar; Wiwik Novitasari; Yulia Anita Siregar (CV Media Inti Teknologi, 2022)
The problem in this study is how the Learning With Quiz Team strategy affects students' reasoning ability and mathematical learning outcomes in the pandemic era. Where this research was conducted at SMA Negeri 6 Padangisidimpuan, this study aims to determine the differences and influences of learning with the Quiz Team on the reasoning ability and learning outcomes of students in mathematics subjects at SMA Negeri 6 Padangsidimpuan. This type of research is quasi-experimental, in this study researchers used Classroom as a learning medium during a pandemic. Where the subjects in this study were students of class X-IPA SMA Negeri 6 Padangsidimpuan. The data collection tool used in this study was a test. The results of this study show that learning with the Learning With Quiz Team strategy has a significant influence on students' reasoning ability and mathematical learning outcomes by 82.05%. From the results of the SPSS test that the value of tcounts>tthe table. Thetable t value of 1.685 is obtained from the value of N 40-2=38. Where the value of 38 has atable t value = 1.685. Since tcount>ttable = 5,776>1,685, then H0 is rejected H1 is accepted. Thus the results of this study show that learning with the Quiz Team can improve students' reasoning skills and mathematical learning outcomes in the pandemic era.